Di Balik Layar: Interpretasi Artistik Pengendalian Diri Penderita Smiling Depression - Safitri, Mesy Nadia; Loravianti, Susasrita; Ilham, Kurniadi; Emri, Emri (Laga-Laga : Jurnal Seni Pertunjukan, 2025)
The dance work Behind the Screen is inspired by a social phenomenon, namely Smiling Depression, a term that refers to a person with depression who looks smiling when experiencing problems, this is often found in social life, they will look normal and happy in living their lives, and will even convince others that they are fine. The creator describes this idea in group choreography using seven female dancers as an interpretation of the different forms of self-control of people with Smiling Depression. The creation of the dance work Behind the Screen provides awareness for someone suffering from Smiling Depression who can control themselves so that it does not have a negative impact on life. This work uses the Alma M. Hawkins dance creation approach in the book "Creating Through Dance and Choreography Form, Technique, and Content, this approach has stages, namely data collection and field observation, exploration, improvisation, formation, and evaluation. The music used in this work is made from computer technology. This work is also strengthened by the use of lighting as a form of emotional depiction of people with Smiling Depression. The dance work Behind the Scenes uses a dramatic style and is performed on the stage of the Boestanoel Arifin Adam Auditorium.